Literature Review: Ethical Perspectives in the Development of Artificial Intelligence and Recommender Systems - Utami, Sri Farida; Elmunsyah, Hakkun; Widiyaningtyas, Triyanna (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The development of Artificial Intelligence (AI) and recommendation systems has had a major impact on various digital service sectors, including social media, e-commerce, and healthcare. Although this technology offers efficiency and personalised services, its implementation also raises complex ethical challenges, such as privacy protection, algorithmic bias, and system accountability. This study aims to analyse ethical perspectives in the development of AI and recommendation systems through a literature review approach. The methods used include analysis of various scientific articles classified into several main ethical dimensions, namely data privacy and security, algorithmic fairness, social media and recommendation systems, digital communication, and educational and publication ethics. The results of the study show that issues of privacy, transparency, and the potential for user behaviour manipulation are dominant issues. Ethics in AI no longer functions solely as an individual value, but as the foundation of responsible and sustainable institutional governance.